2014
DOI: 10.1016/j.stemcr.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Derived Neural Stem Cells Act via Kinase Inhibition to Exert Neuroprotective Effects in Spinal Muscular Atrophy with Respiratory Distress Type 1

Abstract: SummarySpinal muscular atrophy with respiratory distress type 1 (SMARD1) is a motor neuron disease caused by mutations in the IGHMBP2 gene, without a cure. Here, we demonstrate that neural stem cells (NSCs) from human-induced pluripotent stem cells (iPSCs) have therapeutic potential in the context of SMARD1. We show that upon transplantation NSCs can appropriately engraft and differentiate in the spinal cord of SMARD1 animals, ameliorating their phenotype, by protecting their endogenous motor neurons. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…Nevertheless, these studies were able to nicely show promising properties of engrafted cells in the injured spinal cord environment, including synaptic integration into endogenous neuronal circuitry (Fujimoto et al, 2012; Nori et al, 2011). iPS cell-derived NSCs have also shown therapeutic promise in models of other spinal cord diseases such as spinal muscular atrophy (Simone et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these studies were able to nicely show promising properties of engrafted cells in the injured spinal cord environment, including synaptic integration into endogenous neuronal circuitry (Fujimoto et al, 2012; Nori et al, 2011). iPS cell-derived NSCs have also shown therapeutic promise in models of other spinal cord diseases such as spinal muscular atrophy (Simone et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the injected cells demonstrated the ability to differentiate into motor neurons, migrate and send their axons into the white matter and anterior horn and provided evidence of a remarkable amelioration of the neurogenic atrophy phenotype without preventing the premature death of the nmd mice 42. The hypothesis, based on the observed data, is that this improvement may be due to the production of neurotrophins (GDNF, BDNF, NT-3 and TGF-α) and the inhibition of HGK and GSK-3 kinases 31. We observed that the treated nmd mice had higher body weights and lengths and better motility, as measured by the rotarod test.…”
mentioning
confidence: 91%
“…The factors Oct3/4, Sox2, c-Myc and Klf4 act together to overwhelm skin gene expression in fibroblasts and can activate genes encoding hESC proteins, thus inducing the reprogramming of somatic cells into iPSCs 28. Our group provided one of the first descriptions of the generation of IGHMBP2-mutated iPSCs from SMARD1 patients for in vitro studies of SMARD1 31,32. Our group provided one of the first descriptions of the generation of IGHMBP2-mutated iPSCs from SMARD1 patients for in vitro studies of SMARD1 31,32.…”
mentioning
confidence: 99%
“…They also found phenotypic improvement due to motor neuron protection, suggesting trophic influences of the transplanted cells. In support of this mechanism, through in vitro co-culturing studies with motor neurons generated from human SMARD1-iPS cells, they reported that iPS cell-derived NSCs increased motor neuron axonal length via neurotrophic factor production [68]. …”
Section: Transplantation Of Ips Cells In Other Spinal Cord Disease Momentioning
confidence: 99%